2011
DOI: 10.1007/s10519-011-9446-5
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Memory Profile of Disorders Associated with Dysregulation of the RAS-MAPK Signaling Cascade

Abstract: In the present study we evaluated long term memory in twenty individuals with molecularly confirmed diagnosis of Noonan syndrome and LEOPARD syndrome, two disorders caused by mutations in genes coding transducers participating in the RAS-MAPK signaling cascade. The profile of explicit long term memory abilities was investigated using PROMEA, which includes a battery of tests specifically developed to assess memory and learning in verbal, visual and spatial domains. Ten individuals (50%) had impaired (≤5th perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 30 publications
4
36
1
Order By: Relevance
“…Furthermore, within the verbal tasks, a significant advantage was seen in delayed recognition memory relative to delayed recall memory. These results are consistent with the finding from Alfieri et al (2011b) that verbal free recall tasks that depend heavily on prefrontal-hippocampal networks are more challenging for children with NS than recognition tasks that rely on more distributed temporal cortical regions. Interestingly, Wingbermühle et al (2012b) did not find significant deficits among adults with NS as compared to a comparison group with respect to verbal delayed recall on a list-learning task or delayed visual recall as measured by the Rey-Osterreith Complex Figure Test (Rey 1941).…”
Section: Memorysupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, within the verbal tasks, a significant advantage was seen in delayed recognition memory relative to delayed recall memory. These results are consistent with the finding from Alfieri et al (2011b) that verbal free recall tasks that depend heavily on prefrontal-hippocampal networks are more challenging for children with NS than recognition tasks that rely on more distributed temporal cortical regions. Interestingly, Wingbermühle et al (2012b) did not find significant deficits among adults with NS as compared to a comparison group with respect to verbal delayed recall on a list-learning task or delayed visual recall as measured by the Rey-Osterreith Complex Figure Test (Rey 1941).…”
Section: Memorysupporting
confidence: 91%
“…Alfieri et al (2011b) reported that 50 % of a cohort of children with genetically confirmed NS demonstrated impaired performance on a verbal free recall task, whereas only 5-20 % demonstrated impairments on visual and spatial recognition memory tasks. Although results of this study suggest that some aspects of memory may be disproportionately affected in NS, it is unclear from this data whether deficits on the verbal task were due to the retrieval (i.e., free recall) demands or the verbal nature of the task.…”
Section: Memorymentioning
confidence: 99%
“…44 Results of a survey 45 show that many patients with Noonan syndrome have impaired or below average performance in a delayed verbal free recall memory task, and that delayed visual recognition memory is recurrently compromised.…”
Section: Organ Dysfunctionmentioning
confidence: 99%
“…, , ; Alfieri et al. ,b). It should be noted, however, that most studies in children with NS did not include controls matched on age, sex, and intelligence level.…”
Section: Introductionmentioning
confidence: 99%